A Meta-Analysis of the Efficacy of Case Management for Substance Use Disorders: A Recovery Perspective - Vanderplasschen, Wouter; Rapp, Richard C.; De Maeyer, Jessica; Van Den Noortgate, Wim (Frontiers in Psychiatry, 2019)
Background Case management is a client-centered strategy to improve the coordination and continuity of service delivery, especially for persons with substance use disorders and multiple and complex needs. This intervention supports individuals by helping them identify needed services, facilitate linkage with services and promote continued retention in services. However, it is questionable whether case management is equally effective in promoting recovery and aspects of personal functioning. The objective was to conduct an updated meta-analysis and to assess whether case management was more effective than treatment as usual (TAU) among persons with substance use disorders (SUD) for improving treatment-related (e.g. successful linkage with and retention in treatment) as well as personal functioning outcomes (e.g. substance use). Methods This meta-analysis focuses on randomized controlled trials that included persons with alcohol or drug use disorders and compared case management with treatment as usual. To be eligible, interventions had to meet core case management functions as defined in the literature. We conducted searches of the following databases to May 2017: the Cochrane Drugs and Alcohol Specialized Register, CENTRAL, PubMed, Embase, CINAHL and Web of Science. Also, reference lists of retrieved publications were scanned for relevant (un)published studies. Results The overall effect size for case management compared to treatment as usual (TAU) across all outcome categories and moments was small and positive (SMD=0.18, 95% CI 0.07 - 0.28), but statistically significant. Effects were considerably larger for treatment tasks (SMD=0.33, 95% CI 0.18 - 0.48) than for personal functioning outcomes (SMD=0.06, 95% CI -0.02 – 0.15). The largest effect sizes were found for retention in substance abuse treatment and linkage with substance abuse services. Moderator effects of case management models and conditions were assessed, but no significant differences were observed. Conclusions The primary results from earlier meta-analyses were supported: case management is more effective than TAU conditions for improving outcomes, but this effect is significantly larger for treatment-related tasks than for personal functioning outcomes. Case management can be an important supplement to available services for improving linkage and retention, although further research is needed to assess its potential for supporting recovery from a longitudinal perspective.